A review of the BCG vaccine and other approaches toward tuberculosis eradication. Issue 8 (3rd August 2021) - Cho, Thomas; Khatchadourian, Christopher; Nguyen, Huy; Dara, Yash; Jung, Shuna; Venketaraman, Vishwanath
ABSTRACT: Despite aggressive eradication efforts, Tuberculosis (TB) remains a global health burden, one that disproportionally affects poorer, less developed nations. The only vaccine approved for TB, the Bacillus of Calmette and Guérin (BCG) vaccine remains controversial because it's stated efficacy has been cited as anywhere from 0 to 80%. Nevertheless, there have been exciting discoveries about the mechanism of action of the BCG vaccine that suggests it has a role in immunization schedules today. We review recent data suggesting the vaccine imparts protection against both tuberculosis and non-tuberculosis pathogens via a newly discovered immune system called trained immunity. BCG's efficacy also appears to be tied to its affect on granulocytes at the epigenetic and hematopoietic stem cell levels, which we discuss in this article at length. We also write about how the different strains of the BCG vaccine elicit different immune responses, suggesting that certain BCG strains are more immunogenic than others. Finally, our review delves into how the current vaccine is being reformulated to be more efficacious, and track the development of the next generation vaccines against TB.